The Great Commandment of Process Safety - Ferjenčík, Miloš; Cardoso Anastácio, Aline; Mašín, Jindřich (My University, 2016)
Authors think that the ten commandments of risk-based process safety can be boiled up into two most general rules which should be followed by any manager.
Veliké přikázání bezpečnosti procesů
Keywords: Process safety; bezpečnost procesů